Foliar application of biofertilizer in semi-hydroponic lettuce fertigated with saline nutrient solution - Guimarães, Itala Tavares [UNESP]; De Assis Oliveira, Francisco; Leal, Caio César Pereira; De Lima Souza, Maria Williane; Alves, Tatianne Raianne Costa (Lepidus Tecnologia, 2020)
Water scarcity in the world is a problem diagnosed especially in countries with large semi-arid regions such as Brazil. Research has been conducted with a view to making use of saline waters as an input for cultivation, particularly in hydroponics, with especial focus on lettuce, the most prominent leafy vegetable in Brazil. The objective of this study was to evaluate the development of lettuce in a semi-hydroponic system fertigated with saline water and under foliar fertilization with biofertilizer. The present study was carried out in a greenhouse located in the experimental area of the Department of Environmental and Technological Sciences (DCAT) of the Federal Rural University of the Semi-Arid Region, in the municipality of Mossoró, RN, Brazil. The experimental design was a randomized complete block design, with treatments arranged in a 2 x 4 factorial scheme, with 4 replicates, two salinity levels of the water used to prepare the nutrient solution (0.5 and 3.5 dS m-1) and four biofertilizer concentrations (0, 20, 40 and 60%) applied by foliar spraying. The evaluated characteristics were: Shoot diameter, stem diameter, number of leaves, fresh mass, dry mass, leaf succulence, leaf area and specific leaf area. The use of saline water to prepare the nutrient solution reduces fresh mass and dry mass production in the lettuce crop. The biofertilizer can be applied through the leaves at concentration of up to 20%, promoting greater plant growth.
Keywords: Hydroponics; Lactuca sativa; Salinity